Gender-salient family conflict talk - Semenyuk, Antonina A.; Семенюк, Антоніна Афанасіївна (IEEE, 2003)
In this paper the analysis of gender aspects of the family dialogue conflict talk within the framework of symmetric relations (husband – wife) is suggested. In recent years the topic of argument has become a significant concern for research on language and communication. Conflict talk is a common practice among humans. We believe that if gender is embedded in society then it should be observeable in talk.
Keywords: Conflict talk; symmetric relations; gender-salient argumentation; family discourse